Effect of comburent ratios on combustion synthesis of Eu-doped β-SiAlON green phosphors - 葛一瑶 田兆波 陈莹 孙思源 张杰 谢志鹏 (Journal of rare earths, 2017)
SiAlON phosphors doped with rare earths have attracted much attention on the application of light emitting diode（LEDs） benefitting from their outstanding thermal stability, chemical stability and broad emission band properties. In this work, Eu-doped β-SiAlON green phosphors with composition Si（5.5）Al（0.5）O（0.5）N（7.5）：0.035Eu^2＋ were prepared by a highly efficient combustion synthesis（CS） method. The effect of comburent ratios（i.e., Si ＆ Al） were systematically investigated by adjusting the starting compositions of reactants. It was confirmed that the ratios of Si and Al reactants had an intense influence on the phase composition, microstructure and photoluminescence properties of as-synthesized phosphors by directly determining the systematic energy in CS. The as-prepared β-SiAlON：Eu^2＋ phosphors featured with high phase purity, uniform particle size of 3–5 μm, well-crystalline morphology and outstanding luminescent properties of green emission under UV or blue excitation were synthesized with 67.5 wt.% ratio of Si and no Al comburent.